How does mother’s working status and number of siblings affect school age child trauma presenting to the emergency department - Dogan, Serkan; Gurmen, Ekim Saglam; Dorter, Melis; Kalafat, Utku Murat; Bildik, Busra; Cander, Basar (International Journal of Research in Medical Sciences, 2019)
Background: The aim of this study was to investigate the effects of mother working status and siblings on school-age child trauma admitted to the emergency department and to investigate school-age traumas. Methods: This prospective study was conducted with the approval of the ethics committee in the emergency department of a training and research hospital. All demographic data of the school-aged children (66 months-18 years) who applied to the emergency department, the location of the trauma, the mechanism of occurrence, the mother’s working status, the presence and number of siblings, the duration of stay in the emergency department, clinical outcome and hospital service cost were recorded. Results: A total of 794 children were included in the study. 263(33.1%) were girls and 531(66.9%) were boys. Soft tissue trauma was the most common (94.3%). The place of the trauma was 62.7% out of school and 37.3% in school. When mother working conditions were analyzed, it was seen that 34.2% did not work. 97.1% of the children had one or more siblings. The most common trauma mechanism (65.6%) was collision and the second (60.6%) was falls. 99.1% of the patients were discharged. The length of stay in the emergency department of the Grade-schooler age group was higher than the Teen age group (p: 0,000). The length of stay in emergency department was higher in patients without siblings (p: 0.017). It was observed that those whose mothers did not work remained in the emergency room longer (p: 0,000). It was found that the ones whose mothers did not work mostly came with trauma mechanism as a result of falling (65.4%) (p: 0.044). Conclusions: Providing education for protection from accidents in schools and out of school to all people, especially children, parents and teachers, and making safe playgrounds with solid floors will minimize accident and injury rates and severity levels.